Reduction of experimental ocular axial elongation by neuregulin-1 antibody - Shi, Xu Han; Dong, Li; Zhang, Rui Heng; Zhou, Wen Da; Li, Yi Fan; Wu, Hao Tian; Li, He Yan; Yu, Chu Yao; Li, Yi Tong; Wang, Ya Xing; Jonas, Jost B.; Wei, Wen Bin (Frontiers in Medicine, 2023)
Background: Since the mechanisms underlying myopic axial elongation have remained unclear, we examined the effect of neuregulin-1 (NRG-1), an epidermal growth factor family member, on myopic axial elongation. Methods: The guinea pigs aged two to three weeks were subjected to bilateral negative lens-induced axial elongation and received weekly intravitreal injections into their right eyes of NRG-1 antibody (doses: 5 µg, n=8; 10 µg, n=8, 20 µg, n=9) or of NRG-1 (doses: 0.05 µg, n=8; 0.01 µg, n=9; 0.2 µg, n=8), underwent only bilateral negative lens-induced axial elongation (myopia control group, n=10), or underwent no intervention (control group, n=10).The contralateral eyes received corresponding intravitreal phosphate-buffered solution injections. One week after the last injection, the guinea pigs were sacrificed, the eyeballs were removed, the thicknesses of the retina and sclera were histologically examined, the expression of NRG-1 and downstream signal transduction pathway members (ERK1/2 and PI3K/AKT) and the mRNA expression of NRG-1 in the retina was assessed. Results: The inter-eye difference in axial length at study end increased (P<0.001) from the normal control group (-0.02±0.09 mm) and the myopia control group (-0.01±0.09 mm) to the low-dose NRG-1 antibody group (-0.11±0.05 mm), medium-dose NRG-1 antibody group (-0.17±0.07 mm), and high-dose NRG-1 antibody group (-0.28±0.06 mm). The relative expression of NRG-1, ERK1/2, and PI3K/AKT in the retina decreased in a dose-dependent manner from the myopia control group to the NRG-1 antibody groups and the normal control group. The relative NRG-1 mRNA expression in the retina was higher (P<0.01) in the myopic control group than in the NRG-1 antibody groups and normal control group. Scleral and retinal thickness decreased from the normal control group to the NRG-1 antibody groups to the myopic control group. After intraocular injection of NRG-1 protein, there was a slight dose-dependent increase in the difference in axial length between the right and left eye, however not statistically significantly, from the normal control group (-0.02±0.09mm) to the high-dose NRG-1 protein group (0.03±0.03mm; P=0.12). Conclusions: Intravitreal NRG-1 antibody application was dose-dependently and time-dependently associated with a reduction in negative lens-induced axial elongation in young guinea pigs.